Respuesta de tres variedades de lechuga (Lactuca sativa L.) Con tres niveles de fertilización en producción hidropónica en la zona de Ibarra, Provincia de Imbabura - Mafla Tapia, Estuardo Garibalde (2015)
The research was conducted in a hydroponic system NFT (Nutrient Film Tchnique) known as "technical nutrient film" design under a continuous flow of a thin layer of nutrient solution through the roots, through a series PVC channels, the experimental site estubo located in the canton Ibarra Ibarra, Imbabura province with coordinates 0 ° 21 '01' 'north latitude and 78 ° 0' 01 '' west longitude at an altitude of 2,221 meters. The objectives were: to evaluate the best response of agronomic performance of three varieties of lettuce with three levels of fertilizer in hydroponic production, identify the level of fertigation to present the best agronomic performance in three varieties of lettuce and perform economic analysis of each treatments evaluated in this study. The material used was three varieties of lettuce Salad Volcano Red, Dark Green and Black Seed Boston Simpson. The studied factors were three levels of fertigation (treatments) and three varieties (subtratamientos). During assay development the split plot design and verification measures used by multiple range test Duncan at 5% probability. The variables were fertigation levels (treatments): measuring pH and electrical conductivity, crop coefficient (Kc). In varieties of lettuce (subtreatments): plant height (cm), root length (cm), number of leaves per plant........